Cultural Adaptation of Evidence-Based Psychotherapies for Common Mental Health Disorders in Pakistan - Anwar, Khan; Amalia, Madihie; Rehman Ullah, Khan (Bentham Science Publishers Pte. Ltd. Singapore, 2024)
In the realm of Mental Health Sciences, the pursuit of attaining psychological well-being is a universal aspiration. However, the path to achieving psychological well-being is significantly shaped by diverse cultural and societal influences. An examination of the current body of literature reveals that most of the evidence-based psychotherapies, such as eye movement desensitization and reprocessing and cognitive behavioral therapy originated in Western and English-speaking cultures. Consequently, these psychotherapies may require distinct cultural adaptations to ensure their efficacy when applied to populations from varying cultural backgrounds. It is within this intricate interplay between culture and psychological well-being that we embark on a journey through the pages of this book.